An original pharmacoepidemiological–pharmacodynamic method: application to antipsychotic‐induced movement disorders. (6th November 2016) - Nguyen, Thi Thu Ha; Pariente, Antoine; Montastruc, Jean‐Louis; Lapeyre‐Mestre, Maryse; Rousseau, Vanessa; Rascol, Olivier; Bégaud, Bernard; Montastruc, François
Abstract : Aims: Pharmacovigilance databases are usually used to detect new potential signals that are relevant for drug safety. They are seldom used for explanatory purposes, e.g. to understand the mechanisms of adverse drug reactions (ADRs). The aim of the present study was to combine pharmacovigilance and pharmacodynamic data to investigate the association between dopamine D2, serotonin 5HT2A, and muscarinic M1 receptor occupancy and the risks of antipsychotic drug (AP)‐induced movement disorders. Methods: First, we performed a case–noncase analysis using spontaneous reports from the World Health Organization (WHO) Global Individual Case Safety Report (ICSR) database, VigiBase®. We thus measured the risk of reporting movement disorders compared with all other ADRs [expressed as a reporting odds ratio (ROR)] for APs. Second, we performed a linear regression analysis to explore the association between the estimated risk of reporting for individual drugs and their receptor occupancy properties, for D2, 5HT2A and M1 receptors. Results: Compared with second‐generation APs, first‐generation APs were found to be significantly more associated with the reporting of movement disorders in general but also with dystonia, Parkinsonism, akathisia and tardive dyskinesia, irrespective of gender. A significant inverse correlation was found between the ROR for movement disorders and the receptor occupancy of 5HT2A [ P < 0.001; R 2 = 0.51; slope = −0.014; 95% confidence interval (CI) (−0.029, 0.001)], M1 ( P < 0.001; R 2 = 0.56; slope = −0.014; 95% CI (−0.028, 0.001) but not D2 dopamine ( P = 0.54; R 2 = 0.02; slope = −0.003; 95% CI (−0.007, 0.001) receptors. Conclusions: Using the example of AP‐induced movement disorders, the present study underlines the value of the pharmacoepidemiological–pharmacodynamic method to explore ADR mechanisms in humans and real‐life settings.